THE EFFECT OF PAIR TRAINING VARIATION ON THE SEPAK SILA SKILL OF TAKRAW ATHLETES - Agussalim Agussalim; Suaib Nur; Puspa Sari (JURNAL PENDIDIKAN GLASSER, 2023)
The skill of Sepak sila is one of the basic techniques in the game of takraw. The focus of this research is extracurricular students at SMA Negeri 1 Palopo. The problem is the lack of variation in pair training. The purpose of this study is to determine whether or not there is an impact of variations in pair training on the sepak sila skills of the takraw extracurricular students at SMA Negeri 1 Palopo. The term "quantitative research using experimental methods" refers to a method for determining, under controlled conditions, how one treatment affects another treatment. In SMA Negeri 1 Palopo there are 25 male students who take part in takraw extracurricular activities. Purposive sampling was used as a sampling method, meaning that each student will be included in the research sample based on the special considerations of the researcher. SPSS application program version 23 is used for data analysis methods. With a t = count 22.733, this value is greater than t = table 2.059 or t = count 22.733 > t = table 2.059, and the result is sig. (2-tailed) of 0.000 <0.05. The results showed that there were variations in pair training for students' sepak sila skills in the extracurricular sepak takraw at SMA Negeri 1 Palopo. This shows that variations in pair training have a significant effect on the sepak sila skills of the takraw extracurricular students of SMA Negeri 1 Palopo. 059 or t = count 22.733 > t = table 2.059, and the result is sig. (2-tailed) of 0.000 <0.05. The results showed that there were variations in pair training for students' sepak sila in the extracurricular sepak takraw at SMA Negeri 1 Palopo.